The Pesantren Environment as a Determinant of Learning Independence Students (Program Studi Magister Pendidikan Agama Islam Universitas Hasyim Asy’ari Tebuireng Jombang m Asy'ari, 2025)
Learning independence is an essential competence that needs to be developed from the primary school level, as it plays a crucial role in shaping learning habits, responsibility, and students’ self-regulation. This study aims to analyze the pesantren environment as a determinant of learning independence among students aged 7–12 years. The research employed a quantitative approach with an ex post facto correlational design. The research subjects consisted of 30 students residing at Pesantren Abdul Hadi Jombang. The independent variable was the pesantren environment, which included learning facilities, social interaction, disciplinary systems, and religious learning culture, while the dependent variable was students’ learning independence, encompassing time management, learning motivation, initiative, and learning responsibility. Data were collected using a Likert-scale questionnaire and analyzed through descriptive statistics and Spearman correlation analysis. The results indicate that the pesantren environment is categorized as good, with an average score of 3.23, while students’ learning independence is also categorized as good, with an average score of 3.05, although variations were found across several indicators. Correlation analysis reveals a positive and statistically significant relationship between the pesantren environment and students’ learning independence, with a moderate level of association. These findings suggest that the pesantren environment functions as a statistical determinant in the development of learning independence among primary school–aged students. This study underscores the importance of structured, disciplined, and developmentally adaptive guidance in fostering learning independence among children.